Constructing representative group networks from tractography: lessons from a dynamical approach - Kritikaki, Eleanna; Mancini, Matteo; Kyriazis, Diana; Sigala, Natasha; Farmer, Simon F.; Berthouze, Luc (Frontiers in Network Physiology, 2024)
Human group connectome analysis relies on combining individual connectome data to construct a single representative network, which can be used to describe brain organisation and identify differences between subject groups. Existing methods adopt different strategies to select which network structural features to retain or optimise at group level. In the absence of ground truth, however, it is unclear which structural features are the most suitable, and how to evaluate the consequences on the group network of applying any given strategy. In this investigation, we considered the impact of de@ining a connectome as representative if it can recapitulate not just the structure of the individual networks in the cohort tested but also their dynamical behaviour, which we measured using a model of coupled oscillators. We applied the widely used approach of consensus thresholding to a dataset of individual structural connectomes from a healthy adult cohort to construct group networks for a range of thresholds and then identi@ied the most dynamically-representative group connectome as that with the least deviation from the individual connectomes given a dynamical measure of the system.We found that our dynamically-representative network recaptured aspects of structure that it did not speci@ically optimise for, with no signi@icant difference to other group connectomes constructed via methods which did optimise for those metrics.Additionally, these other group connectomes were either as dynamically representative as our chosen network, or less so. While we suggest that dynamics should be at least one of the criteria for representativeness, given that the brain has evolved under the pressure to carry out speci@ic functions, our results suggest that the question regarding which of these criteria are valid and testable persists.